Integrating Qur’anic Values Through Da’wah Interpretation: Reframing the Islamic Education Curriculum for Generation Z’s Moral Challenges - Mashud Mashud; Rudi Trianto; Cecep Soleh Kurniawan; Moh. Syahri Sauma (International Journal of Educational Narratives, 2026)
Background. The moral crisis of Generation Z in the digital era is shaped by the interaction of cultural globalization, algorithmic media exposure, fragmented religious authority, and weak value internalization in conventional Islamic education. These conditions require a curriculum framework that can translate Qur’anic values into ethical reasoning, communicative practice, and digital responsibility. Purpose. This study analyzes how da’wah-oriented tafsir can serve as a foundation for an Islamic education curriculum that responds to the moral challenges of Generation Z. It also formulates a conceptual model for integrating Qur’anic values into curriculum design, pedagogy, institutional culture, and authentic assessment. Method. The study employs a qualitative, PRISMA-informed systematic literature review of peer-reviewed publications from 2020 to February 2026. Searches were conducted in Scopus, DOAJ, Google Scholar, Crossref, Garuda, and Dimensions using keywords related to tafsir, da’wah, Islamic education curriculum, Generation Z, digital literacy, and moral education. Forty-six core studies were synthesized through thematic content analysis. Results. The synthesis indicates that da’wah-oriented tafsir can strengthen Islamic education through five interrelated components: thematic and maqasid-based interpretation, communicative da’wah pedagogy, participatory and problem-based learning, critical digital literacy, and institution-wide habituation of Qur’anic values. The proposed model positions tafsir not merely as text explanation but as a transformative curriculum logic. Conclusion. Da’wah-oriented tafsir offers an adaptive and ethically grounded foundation for Islamic education in the digital era. Its contribution lies in connecting Qur’anic interpretation, da’wah communication, and curriculum practice to support moral reasoning, religious moderation, social responsibility, and digital da’wah competence among Generation Z.